COMMUNITY SERVICE : ENTREPRENEURSHIP POTENTIAL THROUGH COOPERATIVES IN INDONESIA AND MALAYSIA - Toni Hidayat; Abu Bakar Bin Busmah; Anggia Sari Lubis; Ratna Sari Dewi; Debby Cyntia Ovami; M. Rasyid Sidik; Camelya Adelyani (RADJA PUBLIKA, 2023)
Objective from devotion This is For build awareness for entrepreneurs in to move economy through cooperatives in Indonesia and Malaysia. MEA 2025 is continuation from MEA 2015 and aiming For make ASEAN economy is growing integrated And cohesive ; empowered competition And dynamic ; improvement connectivity And Work The same sectoral ; resilient , inclusive , oriented as well as centered on public ; and global ASEAN. Coverage Work The same economy ASEAN : Work The same ASEAN economy covers field industry , trade , investment , services And transportation , telecommunications , tourism , and finance . Besides that , work The same This covers field agriculture And forestry , energy and minerals, as well as business micro small And medium (SMEs). Since 2016, the Ministry of Cooperatives and SMEs has acted as a focal point in the ASEAN Coordinating Committee on Micro, Small, and Medium Enterprises (ACCMSME) cooperation . The cooperation forum bridges the synergy and integration of work programs at the ASEAN level with national work programs, especially in the development of MSMEs. The participation of the Ministry of Cooperatives and SMEs in ACCMSME is realized through involvement in MSME development activities and programs implemented in ASEAN member countries, which refer to the ASEAN Strategic Action Plan for MSME Development (Strategic Action Plan on SMEs Development) . Opportunities economy This can of course be utilized by cooperatives whose business units are included in micro, small and medium enterprises (MSMEs). The approach that can be done in diversifying products and increasing competitiveness through the development of Cooperative Business. This approach is very appropriate because cooperatives can be done en masse based on the potential of UMKM actors.